On coexisting, mending and imagining: notes on the domestics of performance (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
In this essay, the Italian writer, researcher, and educator Giulia Palladini invites us to rethink the linguistic saturation resulting from the use of the binomial performance and politics, by proposing what she calls the domestics of performance. Therefore, the author resorts to non-domesticated notions of the domestic, with the aim of investigating ways to shift the politics of performance to the domestics of performance. Thus, the author intends to demonstrate that feeling at home can be a way of evoking the power of performance to invent other manners of imagining, repairing, and coexisting.
Keywords: performance; politics; domestics; coexistence